Electromagnetic Performance due to Tooth-tip Design in Fractional-slot PM Brushless Machines - Mohd Luqman Mohd Jamil; Zulfikri Zaki Zolkapli; Auzani Jidin; Raja Nor Firdaus Raja Othman; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Permanent Magnet (PM) machines are favorable as an alternative to other machine topologies due to simpler construction and high torque density. However, it may result hight torque ripple due to an influence of cogging torque and electronic commutation. In this paper, comparisons of phase back-emf, static torque and cogging torque due to influence of tooth-tip asymmetry in 12-slot/10-pole double-layer and 12-slot/10-pole single layer winding machines are carried out using 2D Finite-Element Analysis. At rated condition, the stator asymmetry has great influence on the torque performance as there is significant reduction of torque ripple in 12-slot/10-pole mahine equipped with single layer winding than one equipped with double layer winding machine. It si confirmed that an optimum torque performance is desirable via stator iron modification in PM machines.